Key Tecbnology Discussion of Live and VOD Streaming Service Provided on tbe 4G Network - Weijia Shi; Guanzhong Lv (Dianxin kexue)
With the development of 4G networks,telecom operators are urgent to find the service that can use the high speed broadband.Video streaming service became the first choice.But providing video streaming service on the 4G network,operators faced many technical problems like network architecture changing,1arge flow concurrency,multicast solution,content distribution,UE's ability and so on.And the key resource requirement and technology suggestion of providing video streaming service on 4G networks were studied and proposed,based on the analysis of current network status.At the same time,the feasibility analysis of the service deployment was also given,and then some references were provided to operators.